Membangun Komunitas Belajar yang Beriman Melalui Pojok Literasi Rohani di SMPK Adisucipto Penfui - Matilda Suryati Murni; Angela Dewinsa Lawa; Mariana Mau; Meriana Naibahas; Aplonia Nelci Ke Lomi (Universitas Kristen Indonesia Toraja, 2025)
, A spiritual literacy corner is a unique area or space to facilitate reading and learning about religious and spiritual values. The title of this article is